Analisis kebutuhan media pada pembelajaran teks eksplanasi di SD - Restu Nana Irawan; Seni Apriliya; Agnestasia Ramadhani Putri (COLLASE (Creative of Learning Students Elementary Education), 2024)
Abstract Indonesian language subjects, especially explanatory text material, are compulsory lessons for elementary school students listed in the 2013 curriculum. Explanation text learning activities require careful planning of learning activities in order to achieve the desired learning objectives. Achieving learning objectives can be achieved if the teacher is able to choose the right learning methods and media. This study aims to reveal the need for media in learning explanatory text in grade V elementary school. This research was conducted through a qualitative approach with descriptive methods. Data collection techniques were carried out through interviews and observations at one of the elementary schools in Ciamis Regency. The results of the research based on the results of interviews and observations show data that there are limitations to learning media such as only using teacher and student thematic books in the learning process and using newspaper media. In addition, students prefer visual learning with play learning methods. Therefore, it is necessary to develop learning media on explanatory text material in accordance with these characteristics. Keywords: Explanation text, Learning media, Grade V students. Abstrak Mata pelajaran bahasa Indonesia terkhusus materi teks eksplanasi menjadi pelajaran wajib bagi peserta didik sekolah dasar yang tercantum dalam kurikulum 2013. Kegiatan pembelajaran teks eksplanasi diperlukan perencanaan kegiatan belajar yang matang agar dapat mencapai tujuan pembelajaran yang diinginkan. Pencapaian tujuan pembelajaran dapat tercapai apabila guru mampu memilih metode dan media pembelajaran yang tepat. Penelitian ini bertujuan untuk mengungkap kebutuhan media dalam pembelajaran teks eksplanasi di kelas V SD. Penelitian ini dilaksanakan melalui penekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data yang dilakukan melalui wawancara dan observasi di salah satu SD di Kabupaten Ciamis. Adapun hasil penelitian yang didasarkan pada hasil wawancara dan observasi menunjukkan data bahwasannya terdapat keterbatasan media pembelajaran seperti hanya menggunakan buku tematik guru dan siswa dalam proses belajar serta menggunakan media koran. Selain itu, siswa lebih menyukai pembelajaran secara visual dengan metode belajar bermain. Oleh karena itu, diperlukan pengembangan media pembelajaran pada materi teks eksplanasi yang sesuai dengan karakteristik tersebut. Kata Kunci: Teks eksplanasi, Media pembelajaran, Peserta didik kelas V SD.